2020
DOI: 10.1016/j.measurement.2020.107682
|View full text |Cite
|
Sign up to set email alerts
|

3-D printed primary standards for calibration of microwave network analysers

Abstract: This paper describes the design, fabrication and testing of 3-D printed primary standards for use with the calibration of microwave vector network analysers. The standards are a short-circuit and a quarter wavelength section of line that are designed for use with the Thru-Reflect-Line calibration technique. The standards are realised in metal-pipe rectangular waveguide, covering the frequency range from 12 GHz to 18 GHz (i.e., Ku-band). The standards are polymer-based 3-D printed, which is subsequently metal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Their main advantages includes the low cost, the possibility of great customization, the rapid prototyping, the design flexibility or the possibility of combining materials. Concretely, in microwave area, several designs have been proposed for different purposes [1]- [4]. Mechanical properties are usually available from manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…Their main advantages includes the low cost, the possibility of great customization, the rapid prototyping, the design flexibility or the possibility of combining materials. Concretely, in microwave area, several designs have been proposed for different purposes [1]- [4]. Mechanical properties are usually available from manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…The method used estimates the propagation constant of 2-port transmission lines in broadband. It is based on the one proposed by Bianco and Parodi in [28] and later used in TRL calibration [29], [30] to get the propagation constant value.…”
Section: Description Of Methods Based On Transmission Lines Of Differ...mentioning
confidence: 99%
“…At the measurement ports, the rectangular waveguide flanges are based on WR-62 standards, operating at Ku-band, having internal cross-sectional dimensions of a = 15.7988 mm and b = 7.8994 mm. This band is suitable for PolyJet 3-D printing, as issues associated with 3-D print accuracy and surface roughness are negligibly small for most applications [8]- [10]; the latter improving with metallization.…”
Section: B Waveguide Transitionsmentioning
confidence: 99%
“…This enabling technology has already proven itself with metal-pipe rectangular waveguides (MPRWGs) and associated components. For example, the authors have already demonstrated waveguides using various polymer-based 3-D printing technologies: fused deposition modelling (FDM) at X-band (8 to 12 GHz) [6], [7]; polymer-jetting (PolyJet) at Kuband (12 to 18 GHz) [8]- [10]; stereolithographic apparatus (SLA) at W-band (75 to 110 GHz) [6]; PolyJet in the WM-570 band (325 to 500 GHz) [11]; and RECILS in the WM-380 band (500 to 750 GHz) and WM-250 band (750 GHz to 1.1 THz) [12]. More recently, the authors have also demonstrated the use of FDM, SLA and ultra-low cost masked stereolithographic apparatus (MSLA) in polymerbased 3-D printed G-band (140 to 220 GHz) quasi-optical components and integrated subsystems [13].…”
Section: Introductionmentioning
confidence: 99%